3D Nanofabrication via Chemo‐Mechanical Transformation of Nanocrystal/Bulk Heterostructures. Issue 22 (15th April 2018) - Zhang, Mingliang; Guo, Jiacen; Yu, Yao; Wu, Yaoting; Yun, Hongseok; Jishkariani, Davit; Chen, Wenxiang; Greybush, Nicholas J.; Kübel, Christian; Stein, Aaron; Murray, Christopher B.; Kagan, Cherie R.
Abstract: Planar nanocrystal/bulk heterostructures are transformed into 3D architectures by taking advantage of the different chemical and mechanical properties of nanocrystal and bulk thin films. Nanocrystal/bulk heterostructures are fabricated via bottom‐up assembly and top‐down fabrication. The nanocrystals are capped by long ligands introduced in their synthesis, and therefore their surfaces are chemically addressable, and their assemblies are mechanically "soft, " in contrast to the bulk films. Chemical modification of the nanocrystal surface, exchanging the long ligands for more compact chemistries, triggers large volume shrinkage of the nanocrystal layer and drives bending of the nanocrystal/bulk heterostructures. Exploiting the differential chemo‐mechanical properties of nanocrystal and bulk materials, the scalable fabrication of designed 3D, cell‐sized nanocrystal/bulk superstructures is demonstrated, which possess unique functions derived from nanocrystal building blocks. Abstract : High‐yield, functional 3D cell‐sized machines are achieved by ligand‐chemistry‐induced folding of planar nanocrystal/bulk heterostructures. Design rules are established to fabricate various 3D architectures and unique physical functions can be incorporated through careful selection of nanocrystals. This technique promises to find applications in a variety of fields including artificial motors, nanorobots, and chiral optical metasurfaces.